Pushing Back the Limits of Implant Dentistry by Combining Anatomo-Physiological Root-form Implants and Diskimplants with Stem Cell Activation - Scortecci, Gérard; Odin, Guillaume (The Journal of Dentists, 2019)
Treatment of patients with extremely resorbed jaws is a major public health challenge. Anatomo-physiological Diskimplants (APD) and microthreaded, self-tapping, smooth surface root-form implants (APR) were developed in the early 2000s to overcome these difficulties. Used with an immediate functional loading procedure, patients can be equipped with fixed teeth 48 hr. post-op. Application of bone matrix Osseotensors to activate the patient’s own stem cells improves both the initial bone quality and neoangiogenesis, thereby reinforcing the highly atrophic recipient bone sites for placement of these implants. This combined approach allows the surgeon to manage completely resorbed jaws in a much simpler and safer manner than previously thought possible.